2022
DOI: 10.46328/ijte.282
|View full text |Cite
|
Sign up to set email alerts
|

Self-Leadership and Leisure Management of Sports Science Students in the Online Education Process

Abstract: The aim of this research is to examine the self-leadership and leisure management of the students of the Faculty of Sports Sciences in the online education process. The sample group of the research is formed from the students studying in different departments of Afyon Kocatepe University, Faculty of Sports Sciences, in the 2020-2021 academic year, a total of 195 students, including 97 female and 98 male.  As a data collection tool, "Self-Leadership Scale", "Leisure Management Scale" and "Personal Information F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Exercise may train togetherness, make individuals happy, and help a team establish unity and be good for the body (Verawati, Dewi, & Ritonga, 2021). Physical education is one of the intentional efforts to create an environment that can affect learners' potential and lead to positive behavior through physical activity (Akhmad & Mesnan, 2019;Atilgan & Tukel, 2021 ;Karagöz, Dinç, & Kaya, 2022;Ye et al, 2021). The implementation of physical education and sports is a long-term investment to improve the quality of human resources (Irwanto, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise may train togetherness, make individuals happy, and help a team establish unity and be good for the body (Verawati, Dewi, & Ritonga, 2021). Physical education is one of the intentional efforts to create an environment that can affect learners' potential and lead to positive behavior through physical activity (Akhmad & Mesnan, 2019;Atilgan & Tukel, 2021 ;Karagöz, Dinç, & Kaya, 2022;Ye et al, 2021). The implementation of physical education and sports is a long-term investment to improve the quality of human resources (Irwanto, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The learning model used is statistically proven to increase the ability of rhythmic activity in students. The research shows that technology and other variables can be considered in sport education (Atilgan & Tukel, 2021;Atilgan & Tukel, 2022;Karagöz et al, 2022). The model is tested using small classes and large classes.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on leisure satisfaction in the literature (Agate et al, 2009;Dick et al, 1981;Karagöz et al,2022). In a study (Gül, 2019), it was determined that university students' leisure satisfaction had an effect on life satisfaction, while another study (Ardahan & Lapa, 2010) revealed that in addition to this effect in university students, leisure satisfaction differs according to income.…”
Section: Leisure Time Satisfactionmentioning
confidence: 99%